Sosialisasi Etika Lingkungan dan Kesadaran Kesehatan pada Anak di SDN Kebayan - Asri Reni Handayani; Nur Arifatus Sholiha; Rafi’ah Rafi’ah; Ana Lestari (Lembaga Pengembangan Kinerja Dosen, 2025)
The socialization of environmental ethics and environmental health awareness in children is a strategic step in forming a generation that cares, is responsible, and oriented towards the sustainability of natural resources. Children, as a growing age group, have great potential to internalize environmental values and apply them consistently into adulthood. This socialization activity was carried out in the elementary school environment with an interactive lecture and group discussion approach, designed to encourage active participation and deep understanding. The main goal of the activity is to increase children's environmental literacy, including understanding the importance of maintaining cleanliness, managing waste, avoiding pollution, and maintaining the health of the surrounding environment. The results of the evaluation showed a significant increase in students' knowledge about environmental and health issues, as well as a positive attitude towards environmentally friendly practices. Students show high enthusiasm during the activity, which is reflected in active involvement in discussions and commitment to implementing behaviors that support environmental sustainability. This socialization has proven to be effective in fostering environmental awareness and ethics from an early age, which is an important foundation for sustainable development. By equipping children with environmental knowledge and values, it is hoped that they can become agents of change in their respective communities. This kind of activity needs to be carried out continuously and integrated into the basic education curriculum, so that the impact can be wider and more sustainable. School-based socialization is a relevant and strategic approach in shaping a culture of environmental care in the future.